The use of synthetic materials in the treatment of stress urinary incontinence - Stanek, Robert; Kądziołka, Przemysław; Stanek, Anna M.; Szymanowski, Krzysztof; Wilczak, Maciej (Menopause Review/Przegląd Menopauzalny, 2016)
Stress urinary incontinence is a very serious problem which has been noticed by the WHO. This difficult medical condition poses a serious problem as it affects c.a. 20% of the female population and it increases up to 35% in the group of females over 60 years of age. Since there is no single standard surgical procedure which could solve this problem, numerous synthetic materials are used for the operations. It seems that the materials are effective as they improve the condition of women suffering from stress urinary incontinence. Unfortunately these materials have their shortcomings which might lead to certain post-operative complications. Stress urinary incontinence is a disease which affects the social life of the patients. It has a high percentage of recurrence and causes the patient substantial difficulties with keeping high standards of personal hygiene which is consequence makes it impossible to fulfill their social roles. The etiology of this disease is complex and calls for a cross-disciplinary approach to the problem. As there are no standardized or unanimous treatment methods of stress urinary incontinence, numerous sources based on the clinical experience of many medical centers suggest performing TVT and TOT procedures as the most effective treatment methods. The efficacy of the TOT procedure is about 90.8%.